Kritik Pemikiran Richard C. Martin dalam Studi Agama dan Relevansinya dengan Studi Islam di Indonesia - Huda, Sokhi (Program Studi Studi Agama-Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2014)
Islamic studies periodically has become more mature than other period before. In western countries, the matter of this study becomes so popular in the scope of religious scholars. In this regard, the fact is that the discourses of Islamic studies are needed to response any problems, challenges that comes ahead. For Islamic studies variety of scientific approach and method develops due to the emerged multiple perspectives, tendency and orientation externalized from each methodologist. This scheme is actually prompted various methodological problems in relation with paradigm, method and phenomenology. This paper is trying to trace and find two pivotal things which become the basic idea of Richard Martin's thoughts. First is about the main description of Richard martin in relation with Islamic studies and second is methodological insight presented by martin in terms of Islamic studies. The keyword of Richard C. Martin’s ideas is “Data Fields”. It plays as a constructive criticism for Islamic Studies. His view maintains the issues on religious studies and the responds of Muslim writers. It also touches the themes of scripture and prophet, ritual and community, religion and society, scholarship and interpretation, challenge and criticism.